Driving Employee Performance: The Role of Transformational Leadership, Workload, and Motivation at Malang’s Cooperative and Trade Office - Yusuf Abdurrahman; Tanto G. Sumarsono; Sugeng Haryanto (Innovation Business Management and Accounting Journal, 2026)
This study explores the dynamics between transformational leadership, workload, and employee performance within the Malang City Office of Cooperatives, Industry, and Trade. Recognizing that performance gaps in the public sector often stem from imbalanced workloads and leadership approaches, this research specifically examines how work motivation acts as a vital bridge in these relationships Using a quantitative approach and Structural Equation Modeling (SEM-PLS), the study analyzed data from 121 civil servants. The findings reveal that transformational leadership and managed workloads are powerful drivers of motivation. Furthermore, the results indicate that leadership, workload, and motivation each have a direct, positive impact on overall performance. Notably, work motivation serves as a key mediator; it is the psychological engine that transforms organizational inputs and leadership guidance into tangible results.The evidence suggests that achieving peak performance requires more than just administrative adjustments. It demands a holistic strategy that balances optimized task distribution with inspiring leadership to foster a motivated workforce. These insights provide a roadmap for public sector organizations to improve productivity through competency-based management and a deeper focus on employee well-being.